Polymorphonuclear Leukocyte Apoptosis Is Inhibited by Platelet-released Mediators, Role of TGFβ-1 - Brunetti, Mauro; Martelli, Nicola; Manarini, Stefano; Mascetra, Nicola; Musiani, Piero; Cerletti, Chiara; Aiello, Francesca B.; Evangelista, Virgilio (Thrombosis and Haemostasis, 2000)
Platelets regulate several polymorphonuclear leukocyte (PMN) functions. We have found that thrombin-stimulated platelets potently inhibited PMN apoptosis. Cell-free supernatant from increasing concentrations of stimulated platelets inhibited PMN apoptosis in a dosedependent manner, with an effect similar to that of corresponding concentrations of platelets. At the plateau, platelet supernatant inhibited PMN apoptosis by 54.6 ± 6.8%, the anti-apoptotic activity being higher than that of GM-CSF and comparable to that of LPS. Neither IL-1ra nor a combination of anti-IL1 α + β mAb affected the activity of platelet supernatant. In contrast a mAb recognizing the active form of TGF-β1 significantly decreased this activity. Moreover, exogenous TGF-β1 inhibited PMN apoptosis in a dose-dependent manner. The active form of this cytokine was indeed present in the supernatant of stimulated platelets at a concentration able to elicit an anti-apoptotic effect. The p38 MAPK inhibitor SB203580 prevented the anti-apoptotic effect of TGF-β1 in a dose-dependent manner. Interestingly, it also prevented the anti-apoptotic effect of IL-1α, but not that of GM-CSF, LPS and dexamethasone. In conclusion, we report for the first time that PMN apoptosis is potently inhibited by platelet-released mediators, that TGF-β1 mediates an important part of this effect, and that p38 MAPK is involved in the TGF-β1 signaling leading to its anti-apoptotic effect. These results provide novel evidence to support the central role of platelets in inflammation.
Keywords: Platelets; neutrophils; apoptosis; inflammation; human